An adaptive motion estimation algorithm for irregular motion of objects - Kajo, I. (Institute of Electrical and Electronics Engineers Inc., 2014)
In this paper, a novel motion estimation method is proposed in order to enhance the block based matching. The enhancement is achieved by eliminating the number of search points, which in turn will reduce the computation complexity of any block based matching method. Relying on the social force model, a predicted direction of the motion vectors can be estimated significantly. Â© 2014 IEEE.